2011
DOI: 10.1186/1749-799x-6-49
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative echocardiogram in hip fracture patients with cardiac murmur- an audit

Abstract: BackgroundAll hip fracture patients with a cardiac murmur have an echocardiogram as a part of their preoperative work-up in our unit. We performed a retrospective audit to assess the impact of obtaining a pre-operative echocardiogram on the management of hip fracture patients.MethodsAll hip fracture patients (N = 349) between 01/06/08 and 01/06/09 were included in the study. 29 patients had pre-operative echocardiogram (echo group). A computer generated randomised sample of 40 patients was generated from N, 'n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 15 publications
0
17
1
Order By: Relevance
“…There was also had no cardiac intervention in those small groups. 18 Other studies have also shown that TTE is not efficacious in predicting cardiac risk in individuals undergoing noncardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was also had no cardiac intervention in those small groups. 18 Other studies have also shown that TTE is not efficacious in predicting cardiac risk in individuals undergoing noncardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found a 1-day-longer stay, with a greater treatment cost of approximately $6,000. 18 Finally, unnecessary testing can result in excessive intervention, as the fact that five participants in the TTE+ group (vs 1 in the TTEÀ) received cardiac catheterization based on TTE wall motion abnormalities exemplifies. No participant received angioplasty or stents or required further surgical cardiac intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac conditions associated with the highest rates of mortality in non‐cardiac surgery include aortic stenosis [13], cardiac failure [5] and pulmonary hypertension [14], all of which are more reliably assessed using echocardiography than clinical examination alone [15, 16]. Transthoracic echocardiography (TTE) is a useful non‐invasive investigation for screening and assessment of cardiac disease and risk, but is not always available before surgery and an associated delay of several days may be common [17–19]. Hence, it is frequently omitted [20] and decision‐making is based on clinical assessment alone, which may be less accurate [15–17, 21].…”
mentioning
confidence: 99%
“…These additional tests were found to be time-consuming, thus prolonging time to surgery and increasing hospital expenses. [1][2][3][4][5] We support the contention that the outcome of atrisk patients will be improved in all the American Society of Anesthesiology Physical Status (ASA) classes in a medical facility that permits early access to surgical intervention. 6 The efforts required to expedite the preparation of this population for prompt surgery are worth the final result of an increased survival rate.…”
Section: Introductionmentioning
confidence: 63%
“…Most of the reported studies involved the patient's cardiac assessment. 1,[3][4][5]10 Medical expenses associated with a patient's evaluation can have a significant impact on the hospital budget. Several studies reported that those expenses can greatly increase after major surgical procedures in various communities up to 32%, with a low intervention rate if at all in this older population.…”
Section: Discussionmentioning
confidence: 99%